2018
DOI: 10.1128/genomea.01507-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of the Type Strain of Macrococcus canis

Abstract: The first complete genome sequence of the recently described Macrococcus canis species has been determined for the strain KM45013T (=DSM 101690T = CCOS 969T = CCUG 68920T = CCM 8748T). The strain was isolated from a dog with rhinitis and contains a putative γ-hemolysin and a mecB-carrying staphylococcal cassette chromosome mec element (SCCmecKM45013).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The potential for horizontal gene transfer (HGT) is also supported by the identification of the mec complex-carrying transposon Tn 6045 on plasmid pMCCL2 (Baba et al, 2009 ). Similar elements were described in other M. caseolyticus strains (Tsubakishita et al, 2010 ) and an SCC mec element independent of Tn 6045 was identified in a chromosome of the recently described Macrococcus canis (Gómez-Sanz et al, 2015 ; Gobeli Brawand et al, 2018 ).…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…The potential for horizontal gene transfer (HGT) is also supported by the identification of the mec complex-carrying transposon Tn 6045 on plasmid pMCCL2 (Baba et al, 2009 ). Similar elements were described in other M. caseolyticus strains (Tsubakishita et al, 2010 ) and an SCC mec element independent of Tn 6045 was identified in a chromosome of the recently described Macrococcus canis (Gómez-Sanz et al, 2015 ; Gobeli Brawand et al, 2018 ).…”
Section: Introductionsupporting
confidence: 74%
“…caseolyticus subsp. nov. CCM 3540 T , sequenced in this study, and M. canis CCM 8748 T (Gobeli Brawand et al, 2018 ). The sequencing and assembly statistics of the whole genome sequences obtained from the type strains are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations